Risk factors associated with low back pain in golfers: A systematic review and meta-analysis - Armour Smith, J.; Hawkins, A.; Grant-Beuttler, M.; Beuttler, R.; Lee, S.-P. (Sports Health: A Multidisciplinary Approach, 2018)
Context: Low back pain is common in golfers. The risk factors for golf-related low back pain are unclear but may include individual demographic, anthropometric, and practice factors as well as movement characteristics of the golf swing. Objective: The aims of this systematic review were to summarize and synthesize evidence for factors associated with low back pain in recreational and professional golfers. Data Sources: A systematic literature search was conducted using the PubMed, CINAHL, and SPORTDiscus electronic databases through September 2017. Study Selection: Studies were included if they quantified demographic, anthropometric, biomechanical, or practice variables in individuals with and without golf-related low back pain. Study Design: Systematic review and meta-analysis. Level of Evidence: Level 3. Data Extraction: Studies were independently reviewed for inclusion by 2 authors, and the following data were extracted: characterization of low back pain, participant demographics, anthropometrics, biomechanics, strength/flexibility, and practice characteristics. The methodological quality of studies was appraised by 3 authors using a previously published checklist. Where possible, individual and pooled effect sizes of select variables of interest were calculated for differences between golfers with and without pain. Results: The search retrieved 73 articles, 19 of which met the inclusion criteria (12 case-control studies, 5 cross-sectional studies, and 2 prospective longitudinal studies). Methodological quality scores ranged from 12.5% to 100.0%. Pooled analyses demonstrated a significant association between increased age and body mass and golf-related low back pain in cross-sectional/case-control studies. Prospective data indicated that previous history of back pain predicts future episodes of pain. Conclusion: Individual demographic and anthropometric characteristics may be associated with low back pain, but this does not support a relationship between swing characteristics and the development of golf-related pain. Additional high-quality prospective studies are needed to clarify risk factors for back pain in golfers.